An analysis of the perceptions of CSR among Bangladeshi Business School students - Ratul, Salim Shadman; Nayma, Jannatul; Rahman, Sadia Binte (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study explores CSR awareness among the University of Bangladesh students, evaluates perceptions based on socioeconomic and demographic aspects, and considers students' CSR awareness when purchasing a product or applying for a job. Research methodology: First, respondents fill out a questionnaire. The replies are then encoded numerically.  The study examines how demographics affect students' CSR attitudes. Quantitative methods are suitable for determining their relationships. Data must be measured mathematically to determine CSR's effect on student decision-making. Results: The study's findings indicate that students have a solid understanding of corporate social responsibility. Also, age affects perceptions, and educational level influences the majority of perceptions, although gender has no impact on students' perceptions. In addition, students typically do not consider the CSR of a company when they purchase a product from that company or apply for a job with that company. Limitations: The questionnaire method of data collection has various drawbacks. Students may dishonestly answer. Emotional responses and feelings cannot be adequately captured in a survey or questionnaire. The problem of selection bias arises when data is taken from a known individual. There are fewer people in the sample than there are in the population. Contributions: Colleges and universities can better evaluate business courses utilizing the study's results. This study can help government agencies coordinate policy-making. Few studies have examined whether students consider a company's CSR when buying a product or applying for a job. This research comments on that problem.